Comparison of chemical composition of juvenile and mature Gigantochloa albociliata - Innasemuthu, Alexander Mathew (2019)
Gigantochloa albociliata is commonly consumed as edible shoots in some countries, including Malaysia. The study aimed to identify the chemical composition of juvenile and matured G.albociliata according to the parts and also to compare the chemical composition of juvenile and matured G.albociliata. Total of seven test have been conducted to check the chemical composition of bamboo which are hot water solubility, cold water solubility, alcohol acetone extraction, lignin content, holocellulose content, cellulose content and ash content. There are no significant difference within the parts (top, middle, and bottom) of juvenile and bottom G.albociliata. Top portion of both juvenile and mature bamboo have the highest content of cold water solubility, hot water solubility, alcohol acetone solubility, holocellulose content, cellulose content, and ash content. Bottom part of both juvenile and mature bamboo have the highest lignin. However there are significance difference of chemical composition between juvenile and mature G.albociliata, except for hot water solubility, lignin and holocellulose content. Hot water, cold water solubility, and ash content are higher in juvenile bamboo. Alcohol-acetone solubility, lignin, holocellulose and cellulose content are higher in mature bamboo.